Students’ Perspectives: E-Learning During Covid-19 Pandemic - melgis dilkawati pratama; nelvia ibrahim (Indonesian Journal of Integrated English Language Teaching, 2020)
The implementation of e-learning during Covid-19 Pandemic raises pro and cons particularly among the university students such as internet access, budget and quota, as well as overload tasks.  However, others think e-learning is the appropriate one to establish the learning process during physical distance regulation as the prevention of Covid-19. This research aims to describe the student perspectives on the implementation of e-learning during Covid-19 Pandemic. The design of this study was quantitative research. 189 university students in Riau, Indonesia participated by snowball sampling technique. The research collected data by employing a questionnaire in the Google form and sharing it through What Sapp. The data was analyzed by the descriptive statistics. The research revealed the implementation of e-learning among the university students was not optimal. The synchronous and asynchronous as the interaction schemes were established separately. Only 10.58% students had experienced both schemes. Furthermore, internet access, and internet quota and budget were the major inhibiting factors. This research expects the educators and stakeholders evaluating the implementation of e-learning and provides comprehensive trainings for educators on e-learning.